2021
DOI: 10.3897/jucs.65202
|View full text |Cite
|
Sign up to set email alerts
|

15-Puzzle Problem Solving with the Artificial Bee Colony Algorithm Based on Pattern Database

Abstract: The N-puzzle problem is one of the most classical problems in mathematics. Since the number of states in the N-puzzle is equal to the factorial of the number of tiles, traditional algorithms can only provide solutions for small-scale ones, such as 8-puzzle. Various uninformed and informed search algorithms have been applied to solve the N-puzzle, and their performances have been evaluated. Apart from traditional methods, artificial intelligence algorithms are also used for solutions. This paper introduces a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Nowadays, metaheuristic optimization algorithms are widely used for solving complex problems [33], [34], [35]. One of the algorithms that have been recently used to obtain non-optimal solutions to the Fifteen Puzzle problems was a metaheuristic algorithm Artificial Bee Colony (ABC) [36]. Here, the BA* algorithm with HH is compared with the ABC algorithm to show that the obtained results of BA* are sufficiently accurate and much nearer to the optimal results.…”
Section: Inadmissible Heuristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nowadays, metaheuristic optimization algorithms are widely used for solving complex problems [33], [34], [35]. One of the algorithms that have been recently used to obtain non-optimal solutions to the Fifteen Puzzle problems was a metaheuristic algorithm Artificial Bee Colony (ABC) [36]. Here, the BA* algorithm with HH is compared with the ABC algorithm to show that the obtained results of BA* are sufficiently accurate and much nearer to the optimal results.…”
Section: Inadmissible Heuristicsmentioning
confidence: 99%
“…To increase the effectiveness and performance of the heuristic function of the ABC algorithm, three heuristics PDB, MD, and LC were combined. The ABC algorithm was run on 25 randomly generated solvable instances of the Fifteen Puzzle but the algorithm did not produce an optimal solution for any of them and it provided solutions that are far from the optimum [36]. Tuncer [36] argued that the results produced by the ABC algorithm are acceptable even though the solution lengths are far from the optimal solution lengths.…”
Section: Inadmissible Heuristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the total number of food sources and the number of bees employed are equal. Another presumption is that the number of bees working and the number of bees watching are equal [33][34][35].…”
Section: Artificial Bee Colony (Abc)mentioning
confidence: 99%
“…R Yao et al found that the hysteresis model is complex and non-differentiable, which leads to the complexity of gradient acquisition, and to solve this problem, the authors proposed an improved ABC and used it for the identification of lag parameters, and finally verified the feasibility of the method in the identification of nonlinear hysteresis parameters, although this method improves the identification performance of nonlinear hysteresis parameters, it does not consider the identification problem of other linear parameters [11]. A Tuncer found that the traditional algorithm, can only provide small-scale solutions for the N-puzzle problem, to achieve the solution of the 15-puzzle problem, the authors proposed a new algorithm built on the metaheuristic algorithm, which divides the puzzle, and uses ABC to solve the divided the results show that the method helps significantly in solving the 15-puzzle problem, this method only divides the problem, simplifies the solving steps, but has little effect on the solving calculation of the problem [12].…”
Section: Introductionmentioning
confidence: 99%